Asymmetric split H-shape resonator array for enhancement of midwave infrared photodetection - Tong, Jinchao (2021)
Midwave infrared (3-5 μm ) photodetector with high detecting performance at room temperature has always been pursued for wide applications such as remote sensing, medical diagnosis, communication, and molecular spectroscopy. However, current detection technology is intrinsically limited by materials and structures. Here, we report an integrated midwave infrared photodetector consisting of an InAsSb-based heterojunction photodiode and an asymmetric split H-shape gold array incorporated on the top surface. The patterned metallic array has the capability to confine light within small volume, leading to strong light absorption in the InAsSb absorber therefore enhanced photoresponse compared to the reference one without patterned metals. Electrically controlled enhancement of photoresponse is observed with maximum enhancement factor of ∼ 3 at-0.2 V applied voltage bias. This integrated photodiode achieves an enhanced room-temperature detectivity of 1.7× 109 Jones under-0.3 V applied voltage bias. In addition, the integrated photodiode demonstrates a rise/fall time of ∼1μs , as fast as the reference one.